Penerapan Inovasi Hijau dalam Perancangan Souvenir Wisata Berkelanjutan Menggunakan Material Biokomposit dari Limbah Tandan Kosong Kelapa Sawit (TKKS) untuk Mendukung Branding IKN sebagai Ibu Kota Negara Terhijau di Dunia - Syaputra, Eko Agung; Parmita, Ade Wahyu Yusariarta Putra; Febrianti, Nia; Maharany, Gunanda Tiara; Rossalina, Novianti (LPPM ITK, 2024)
Souvenirs have an important role in supporting regional economic development, souvenirs can also function as an important symbol of identity and culture because they can contribute to the preservation and promotion of local traditional heritage. But on the other hand, the souvenir industry also has the potential to damage the environment. Therefore, it is important to ensure that souvenir production and consumption practices use sustainable principles. The increasing level of deforestation and forest degradation in East Kalimantan due to IKN development needs to be balanced with green innovation. One of them is exploring renewable materials as raw materials for superior regional products. Indonesia has an abundance of empty oil palm fruit bunches (EFB), for every 1 ton of palm oil there is 23% or 230 kg of EFB waste. With its quality and uniqueness, this EFB biocomposite material is suitable as the basic material for sustainable tourism souvenirs as an Indonesian identity. This research aims to develop sustainable tourist souvenir designs made from EFB waste as one of the branding of IKN souvenirs for the international market. The identification in this research used the Design-driven Material Innovation (DDMI) method. DDMI is a product design design model that starts from material development from understanding material characteristics, and creating product lines, to communicating the uniqueness of materials to the market. This research produces designs and prototypes of tea sets as sustainable tourist souvenir products that are ready to be made on an industrial scale. Tea sets are often used as souvenirs in state agendas because they reflect a country's cultural identity and diplomatic status, as well as a way to strengthen relations between countries through appreciation and respect. This aligns with one of the goals to support the branding of the IKN as the greenest capital city in the world.